Effect of Washing and Drying Conditions on Dimensional Change in Various Articles of Knitted Clothing (Journal of Fiber Bioengineering and Informatics, 2019)
We investigated the effect of washing and drying conditions on dimensional change in various articles ofknitted clothing, taking into account drying temperature, temperature change during drying, externalforce at dehydration, external force during drying, and humidity during drying. We immersed samplesin water at 25 ± 2◦C for 30 min, then dried them in a chamber at 40, 60, and 80 ◦C, and at 5%relative humidity (RH). We also investigated the effects of increasing the temperature from 40 to 60 ◦Cand decreasing it from 60 to 40 ◦C. After dehydration, we dried the samples using a roller and a frontloader washing and drying machine at various humidity levels. We measured dimensional changes inthe samples before and after drying. We investigated five samples of knitted clothing: men’s socks,women’s socks, men’s underwear, women’s underwear, and women’s t-shirts. We detected no differencein the dimensional change ratio in the cotton or polyurethane underwear and t-shirts when the dryingtemperature was varied. However, the dimensional change ratio of acrylic-containing men’s socks varieddepending on the drying temperature. When drying acrylic-containing men’s socks from 40 to 60 ◦C,the dimensional change ratio was larger than under other drying conditions. A lower temperature inthe final drying stage could effectively reduce the shrinkage of socks made from acrylic, polyester, andpolyurethane. The deformation due to external force during dehydration affected dimensional change.The external force during drying also greatly affected dimensional change in the knitted clothing. Thehumidity and drying time did not affect dimensional change in the knitted cotton clothing.
Keywords: Shrinkage; Knitted clothing; Drying temperature; Knitted fabric.